2004
DOI: 10.1159/000077896
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbyl Palmitate Augments Hypoxic Respiratory Response in the Cat

Abstract: The redox signaling is germane for the hypoxia-sensing mechanisms at the carotid body. This raises the strong possibility that agents possess reducing and antioxidant attributes, such as ascorbate, could influence the hypoxic respiratory response. However, water solubility of ascorbate makes its effectiveness at membrane-associated target sites dubious. In this study, we sought to determine the effect of ascorbyl-6-palmitate (AP), a lipid-soluble derivative of ascorbate which penetrates biomembranes, on hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Embora alguns autores citem que o palmitato de ascorbil é totalmente hidrolisado no intestino humano, formando o ácido ascórbico, May et al (1996) indicam que uma pequena fração é absorvida na sua forma íntegra e atua em meio lipídico no metabolismo. Pokorski et al (2003Pokorski et al ( , 2004 observaram, em gatos, a deposição do palmitato de ascorbil após o fornecimento na dieta, e demonstraram que parte do palmitato de ascorbil foi absorvido pelo trato gastrointestinal e depositado sem sofrer mudanças estruturais, similarmente ao ocorrido no presente trabalho. Entretanto, provavelmente a maior parte do palmitato de ascorbil absorvido, na forma de ácido ascórbico derivado da hidrolização do palmitato de ascorbil, resultou nas maiores concentrações de ácido ascórbico nas larvas de dourado, alimentadas com rações com a suplementação de 100 e 1.000 mg kg -1 de palmitato de ascorbil.…”
Section: Resultsunclassified
“…Embora alguns autores citem que o palmitato de ascorbil é totalmente hidrolisado no intestino humano, formando o ácido ascórbico, May et al (1996) indicam que uma pequena fração é absorvida na sua forma íntegra e atua em meio lipídico no metabolismo. Pokorski et al (2003Pokorski et al ( , 2004 observaram, em gatos, a deposição do palmitato de ascorbil após o fornecimento na dieta, e demonstraram que parte do palmitato de ascorbil foi absorvido pelo trato gastrointestinal e depositado sem sofrer mudanças estruturais, similarmente ao ocorrido no presente trabalho. Entretanto, provavelmente a maior parte do palmitato de ascorbil absorvido, na forma de ácido ascórbico derivado da hidrolização do palmitato de ascorbil, resultou nas maiores concentrações de ácido ascórbico nas larvas de dourado, alimentadas com rações com a suplementação de 100 e 1.000 mg kg -1 de palmitato de ascorbil.…”
Section: Resultsunclassified
“…The idea that a redox pathway may be involved in chemoreceptor triggering comes from fi nding ascorbate in the carotid body and its depletion in hypoxia [8]. Pokorski et al [25] examined in an in vivo electrophysiological study the effect of ascorbyl palmitate on hypoxic respiration in anesthetized cats. They reported that treatment with ascorbyl palmitate augments hypoxic respiration.…”
Section: Ascorbyl Palmitate Augments Hypoxic Respiratory Responsementioning
confidence: 99%